Prevalence and clinical profile of celiac disease among malnourished children in South Rajasthan, India - Sharma, Mukesh; Mandot, Sanjay (International Journal of Contemporary Pediatrics, 2018)
Background: Celiac disease (CD) is the most common genetically related food intolerance, worldwide. The objective of this study was to study the prevalence and clinical profile of malnourished children. Methods: It was a prospective and observational study. The present study was conducted in the Department of Paediatrics, Geetanjali Medical College and Hospital, Udaipur, Rajasthan. Two hundred and one children were studied. All malnourished children were initially selected and those fulfilling inclusion criteria were included in the study. A detailed interview of all the children/parents was conducted regarding symptoms commonly associated with celiac disease. All cases found positive for t-TGA (>10au/ml) were subjected to upper GI Endoscopy. Subjects were labelled as celiac disease if tissue trans-glutaminase IgA antibodies were >10 au/ml and histopathology was suggestive. Statistical analysis was done by one way ANOVA test and Chi-square as per requirements also Fisher exact and Man Whitney were applied. Results: Celiac disease was present in 23.9% of malnourished patients. Most common presenting symptoms were diarrhoea (40.2%), abdominal distension (39.9%) and abdominal pain (36.8%) and most common clinical sign was pallor, which was present in more than three-fourth of the patients (85.9%) followed by multivitamin deficiency (25.4%). Conclusions: There is a high prevalence of Celiac disease in malnourished children. Screening for Celiac disease (especially in presence of diarrhoea and abdominal distension, pain abdomen) should be an essential part of work-up in all malnourished children.